2003
DOI: 10.1097/00004836-200303000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Management of the Branch Duct Type Intraductal Papillary Mucinous Neoplasms of the Pancreas

Abstract: These results suggest that the branch duct type IPMNs less than 30 mm and without mural nodules is benign and might be treatable with limited resection or careful observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
2
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(119 citation statements)
references
References 25 publications
4
109
2
4
Order By: Relevance
“…The data in this study also complied with this rule. However, compared with the published series from Europe, Japan, and the USA [9,[29][30][31][32] , the main duct IPMN had a lower rate of malignancy (1 of 3) in the present study, whereas the combined-type IPMNs demonstrated malignancy in more cases (10 of 12) on pathology. The sensitivity, specificity, and accuracy of MDCT in characterizing the malignancy of IPMNs were 100%, 87.5% and 95%, respectively.…”
Section: Discussioncontrasting
confidence: 80%
“…The data in this study also complied with this rule. However, compared with the published series from Europe, Japan, and the USA [9,[29][30][31][32] , the main duct IPMN had a lower rate of malignancy (1 of 3) in the present study, whereas the combined-type IPMNs demonstrated malignancy in more cases (10 of 12) on pathology. The sensitivity, specificity, and accuracy of MDCT in characterizing the malignancy of IPMNs were 100%, 87.5% and 95%, respectively.…”
Section: Discussioncontrasting
confidence: 80%
“…This in turn raises the question of whether branch-duct IPMN (Br-IPMNs) may be a distinct tumor type with altogether different biologic behavior than those arising in the main pancreatic duct. [5][6][7][8][9] Various reports have shown significant differences in the prevalence of cancer in main-duct IPMN (including the mixed type) vs Br-IPMNs (70% vs 25%, respectively). 1,[3][4][5][7][8][9][10][11][12][13] Consequently, some authors have recommended nonsurgical management with close observation for IPMNs that arise from branch ducts and that fail to meet certain "high-risk" criteria.…”
mentioning
confidence: 99%
“…Vari studi dimostrano infatti come nelle IPMN dei dotti principali la progressione verso forme maligne, in situ o invasive, avvenga in una percentuale variabile dal 60% al 92%, con una media del 70%. Sulla base di tali dati, qualora le indagini preoperatorie pongano il sospetto di una IPMN del dotto principale o di tipo misto, l' exeresi chirurgica è di regola indicata [10,11,[14][15][16][17][18][19][20].…”
Section: Figura 1 Immagini Rm/tc Della Lesione Cistica Mucinosa Intrunclassified
“…Decisamente meno frequente è la cancerizzazione delle lesioni interessanti i dotti periferici, riscontrata in una percentuale variabile dal 6% al 46%, con una media del 25% [10,11,[14][15][16][17][18][19]. È da notare, però, come i due studi che descrivono la più alta frequenza di cancro invasivo (30% e 31% rispettiSulla base del referto della TC la paziente è stata sottoposta a colangio-RM (Figura 1).…”
Section: Figura 1 Immagini Rm/tc Della Lesione Cistica Mucinosa Intrunclassified